Enhancing Teacher Self-Efficacy in Multicultural Classrooms and School Climate: The Role of Professional Development in Multicultural Education in the United States and South Korea. (November 2020) - Choi, Soobin; Lee, Se Woong
The modern classroom is becoming increasingly diverse, with many countries seeking to develop teacher self-efficacy in multicultural classrooms (TSMC) to effectively teach diverse students by offering professional development in multicultural education (PDME). Using the Teaching and Learning International Survey 2018, we examine whether the teachers' experience in PDME improves TSMC, as well as whether TSMC mediates the relationship between PDME and teachers' perceptions of school climate in secondary schools in the United States and South Korea. We find a significant positive relationship between PDME and TSMC and that TSMC plays a mediating role between PDME and school climate. The findings suggest that PDME not only plays a key role in enhancing TSMC but also promotes a positive school climate.